OXYRHYNCHUS LOGION (1907) V - Burrows, Eric (The journal of theological studies, 1927)
ERIC BURROWS, S.J.; OXYRHYNCHUS LOGION (1907) V, The Journal of Theological Studies, Volume os-XXVIII, Issue January, 1 January 1927, Pages 186, https://doi.org